First record of Moniliformis moniliformis (Bremser, 1811) (Moniliformida: Moniliformidae) in mice of the genus Apodemus kaup, 1829 (Rodentia: Muridae) in Serbia - Tošić Božana; Čabrilo Borislav; Miljević Milan; Rajičić Marija; Bajić Branka; Budinski Ivana; Bjelić-Čabrilo Olivera (Kragujevac Journal of Science)
As a part of research activities focused on rodent helminth fauna in Serbia, over the previous decade, we registered the presence of a species with zoonotic potential, Moniliformis moniliformis, an acanthocephalan (or spiny-headed worm) intestinal parasite that primarily infects rats, mice, and voles. The adult form of the species M. moniliformis was found in the small intestine of a single striped field mouse (Apodemus agrarius) from Cer Mountain, and two individuals of the yellow-necked mouse (Apodemus flavicollis) from the localities of Donji Milanovac and Senokos. Another species of Acanthocephala, reported in earlier studies of Spermophilus citellus in Serbia, is Macracanthorhynchus hirudinaceus, which also has zoonotic potential. Data on human infection with the acanthocephalans are scarce worldwide, including Serbia, but they should not be ignored.